2012
DOI: 10.14245/kjs.2012.9.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results and Risk Factors for Recurrence of Lumbar Disc Herniation

Abstract: ObjectiveRecurrent lumbar disc herniation has been defined as disc herniation at the same level, regardless of ipsilateral or contralateral herniation, with a pain-free interval greater than 6 months. The aim of this study is to analyze outcomes and identify the potential risk factors for recurrent lumbar disc herniation.MethodsThe authors retrospectively reviewed the cases of 178 patients who underwent open discectomy for single-level lumbar disc herniation. Visual analogue scales and modified Macnab criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 30 publications
3
23
1
Order By: Relevance
“…Various studies have reported HLD recurrence after LD, and 5% to 15% of patients undergo secondary LD [20,24]. Our study reported a 15% incidence of recurrence within a mean of 28.3 months.…”
Section: Discussionsupporting
confidence: 55%
“…Various studies have reported HLD recurrence after LD, and 5% to 15% of patients undergo secondary LD [20,24]. Our study reported a 15% incidence of recurrence within a mean of 28.3 months.…”
Section: Discussionsupporting
confidence: 55%
“…To our knowledge, no previous studies have reported any significant difference or trend toward difference in age between the rLDH group and the non-rLDH group. 7 , 15 , 16 Häkkinen et al reported that the age distribution of all patients in their study group was comparable to that of patients in the rLDH group. However, no mean value was described.…”
Section: Discussionmentioning
confidence: 61%
“… 2 , 7 In contrast, Jung Tae Oh found being female as a statistically significant risk factor of recurrence. 15 Shimia et al concluded that being male could predict rLDH. 8 Both studies, however, included a very small study population.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent lumbar disc herniation (LDH) that develops at least 6 months after previous open discectomy shows a relatively frequent incidence of 7%–10%. 1 2) Surgical options for recurrent LDH could be determined based on the type of previous procedure. If the previous one was percutaneous endoscopic lumbar discectomy (PELD) through a far lateral approach, revision PELD could be performed using a posterior approach despite the high risk of dura tear associated with the use of one portal during the procedure, 3) which requires steep learning curve and special instruments for epidural scarring.…”
mentioning
confidence: 99%